Choir and Apse - Ghosh, Ayan (2023)
James Trubshawe had ambitious plans for a complete makeover of St. Thomas Church, but the plan couldn't be executed in its entirety. Nevertheless, he recognized the emerging trend of Gothic Revival style and incorporated Gothic elements (like stained glass windows) to make the church appear visually consistent with Victorian Gothic buildings in Mumbai.